Unskilled labor for development : its economic cost - McDiarmid, Orville John.; World Bank. (Baltimore : Published for the World Bank [by] the Johns Hopkins University Press, 1977)
The book can be divided roughly into two parts. The first part contains a general discussion of the structure of labor markets in developing countries, followed by a thoughtful critique of the two methods of estimation of the social wage rate: one by M.D. Little and J.A. Mirrless (LM) and the other by P. Dasgupta, A. Sen, and S. Marglin (DSM). The second part consists of a review of labor market conditions in Korea and Taiwan in one chapter and those in Indonesia and the Philippines in another. The book also contains about 60 pages of labor statistics on the four areas mentioned. The main contribution of the book is an estimation of the ratio of the economic or social wage rate (SWR) for unskilled agricultural labor to the market or private wage rate (W) in the non- agricultural sectors of the economies of Taiwan and the Philippines.
Includes bibliographical references: p. 203-206.
rpm 16/04/2018
Loans
Keywords: Wages; Unskilled labor